The Role of Women in Korea: A Review of Historical Milestones (2020)
Women have been a key pillar for the development of Korea. Her traditional role as housekeeper and educator of children allowed certain extent the nation ́s progress, over time her role has changed due to various milestones that allowed her insertion in society along with the establishment of rights formerly reserved exclusively for men. This essay seeks to delve into historical facts that have been essential for the construction of the role occupy by women in Korean society today. Important milestones that have contributed to the distancing of the traditional role oriented towards an area of female liberation in Korean society will be mentioned. Finally, a brief mention to the current situation of Korean women will be made.